The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/16583655.2020.1790912
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial effect and sub-acute toxicity of alkaloid, flavonoid and phenolic extracts ofSida acutaleaf onPlasmodium berghei-infected animals

Abstract: The antiplasmodial and safety profile of alkaloid, flavonoid and phenol extracts of Sida acuta (300 and 600 mg/kgbw) on hepatic and renal integrity of rats were investigated. Alkaloid, flavonoid and phenol extracts produce parasitaemia suppression of 50.83%, 33.50% and 64.64%, respectively. Sub-chronic administration of the phytochemicals caused marked (p < 0.05) dosedependent increase in erythrocytic and leucocytic indices while serum ALP, AST, ALT, albumin, urea and creatinine concentrations compared well (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Interestingly, some Sida secondary metabolites including stigmasterol and its derivative, stigmasterol-3-O-β-D-glucopyranoside, have been shown to exhibit antimalarial properties [53,78]. Similarly, the presence of high levels of flavonoids, alkaloids, terpenoids and tannins which have been known to have antimalarial and chemoprotective activities could be responsible for the findings of the present study [27,79,80]. This study has some limitations such as the inability to track the specific compounds responsible for the antimalarial activities of EESAL and characterize them and inability to evaluate the specific mechanism of killing the parasites by EESAL.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Interestingly, some Sida secondary metabolites including stigmasterol and its derivative, stigmasterol-3-O-β-D-glucopyranoside, have been shown to exhibit antimalarial properties [53,78]. Similarly, the presence of high levels of flavonoids, alkaloids, terpenoids and tannins which have been known to have antimalarial and chemoprotective activities could be responsible for the findings of the present study [27,79,80]. This study has some limitations such as the inability to track the specific compounds responsible for the antimalarial activities of EESAL and characterize them and inability to evaluate the specific mechanism of killing the parasites by EESAL.…”
Section: Discussionsupporting
confidence: 60%
“…Filtrates from the extraction chambers were dried (rotary evaporator at 45 °C), obtaining crude ethanol leaf extract of S. acuta (EESAL) (13.32%). Ethanol was used as a solvent in this study based on the traditional practice where the leaves are soaked in ethanol for 2-3 days and the decoction orally taken for 4-7 days to treat malaria [16,26,27]. In addition, results of pilot study conducted using different solvent extracts showed that ethanol extract has significantly higher activity compared to n-hexane, ethyl acetate, water and chloroform extracts (data not shown).…”
Section: Extraction Of Plant Materialsmentioning
confidence: 99%
“…Evidence for the anti-inflammatory properties of flavonoids and alkaloids have been reported by several studies using different models of inflammation [24][25][26]. The significant anti-inflammatory effects demonstrated by the purified fraction of M. senegalensis leaf could be mechanistically explained by the fact that phyochemicals are known to inhibit the enzymes involved in the production of inflammatory mediator including cyclooxygenase and 5-lipoxygenase pathways [27].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products, particularly medicinal plants have been used from time immemorial for the treatment of various diseases (41)(42)(43) and various studies have recommended the evaluation of medicinal plants in order to accept their use for medicinal purposes (44)(45)(46)(47)(48)(49)(50). It is therefore noteworthy that Dennettia tripetala demonstrated safety profile in toxicity study, in addition to its various biological activities, and thus serve as an important medicinal plant worthy of further preclinical evaluation…”
Section: Toxicity Of Dennettia Tripetalamentioning
confidence: 99%